Use of the multi-organ dysfunction score as a tool to discriminate different levels of severity in uncomplicated Plasmodium falciparum malaria - R. Helbok (2018)
The usual criteria for severe malaria are not always sufficient to identify patients who subsequently develop this disease. The multi-organ dysfunction score (MODS) was assessed in 22 patients with uncomplicated Plasmodium falciparum malaria to test its usefulness in discriminating different severity levels. The MODS on admission was highly correlated with the baseline concentration of tumor necrosis factor-α (r = 0.83, P < 0.001) and the duration of symptoms after admission (r = 0.54, P = 0.01). The MODS was also correlated with parasite count (r = 0.52, P = 0.014), parasite clearance time (r = 0.54, P = 0.009), and fever clearance time (r = 0.58, P = 0.005). The above correlations remained significant after controlling for the initial parasitemia (P = 0.03 and 0.005). The MODS is simple and easy to apply and needs a recording time of less than three minutes. Thus, this score might provide a quantitative approach for determining severity in Plasmodium falciparum malaria.